2012
DOI: 10.4085/1062-6050-47.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Between Copers and People With Chronic Ankle Instability

Abstract: Context: Differences in various outcome measures have been identified between people who have sprained their ankles but have no residual symptoms (copers) and people with chronic ankle instability (CAI). However, the diagnostic utility of the reported outcome measures has rarely been determined. Identifying outcome measures capable of predicting who is less likely to develop CAI could improve rehabilitation protocols and increase the efficiency of these measures.Objective: To determine the diagnostic utility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 29 publications
0
58
0
2
Order By: Relevance
“…Many recent reviews and multifactorial studies have provided important information outlining that there are multiple potential contributing mechanical, neuromuscular, functional, and/or perceived deficits that may persist long after physiologic tissue healing times have elapsed and interventions have been completed following an acute ankle joint sprain. [23][24][25][26][27][28][29][30][31][32][33][34] Consistently, these reviews and multifactorial studies support the proposition that CAI is a multifaceted and complex condition, requiring further indepth interdisciplinary study.…”
Section: International Ankle Consortium Position Statementmentioning
confidence: 63%
“…Many recent reviews and multifactorial studies have provided important information outlining that there are multiple potential contributing mechanical, neuromuscular, functional, and/or perceived deficits that may persist long after physiologic tissue healing times have elapsed and interventions have been completed following an acute ankle joint sprain. [23][24][25][26][27][28][29][30][31][32][33][34] Consistently, these reviews and multifactorial studies support the proposition that CAI is a multifaceted and complex condition, requiring further indepth interdisciplinary study.…”
Section: International Ankle Consortium Position Statementmentioning
confidence: 63%
“…On the other hand, despite lower reliability, outcomes of the dynamic phase may still detect impairments, due to higher effect sizes [6]. This is illustrated by the findings of Wikstrom et al, who showed that the mediolateral stability index had higher accuracy to differentiate between 'copers' and individuals with chronic ankle instability than the other stability indices, whilst having a 'poor' reliability [12,34].…”
Section: Discussionmentioning
confidence: 99%
“…The healthcare burden associated with ankle instability necessitates increased research and clinical outcomes that can be used to reduce the disability and recurrence rates associated with CAI. It is clear from the body of literature that there are many contributing factors to CAI that can create a host of impairments 15,20,21,24,29,28,39,47 ; however, this condition is more heterogeneous than many realize. 15,23 Therefore, researchers need to be cognizant of criteria that are best associated with CAI based on current available evidence.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Previous authors have considered mechanical instability as an explanatory factor for lingering ankle instability, but there has not been a definitive association of ankle laxity with CAI. 6,8,15,20,23,24,28,29,47 Hertel's 20 original model differentiated mechanical instability from functional instability. More recently, Hiller et al,23 refining the model of categorizing CAI, suggested as many as 7 subgroups of individuals with CAI that would likely provide better homogeneity in describing the pathology.…”
Section: 37mentioning
confidence: 99%
See 1 more Smart Citation